2014
DOI: 10.1371/journal.pone.0093460
|View full text |Cite
|
Sign up to set email alerts
|

Urinary TIMP-2 and IGFBP7 as Early Biomarkers of Acute Kidney Injury and Renal Recovery following Cardiac Surgery

Abstract: BackgroundDifficulties in prediction and early identification of (acute kidney injury) AKI have hindered the ability to develop preventive and therapeutic measures for this syndrome. We tested the hypothesis that a urine test measuring insulin-like growth factor-binding protein 7 (IGFBP7) and tissue inhibitor of metalloproteinases-2 (TIMP-2), both inducers of G1 cell cycle arrest, a key mechanism implicated in acute kidney injury (AKI), could predict AKI in cardiac surgery patients.MethodsWe studied 50 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
301
7
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(327 citation statements)
references
References 40 publications
7
301
7
12
Order By: Relevance
“…Biomarkers of AKI, such as NGAL, KIM‐1, and IL‐18, may be potentially beneficial for early detection, diagnosis, and prognosis of AKI after cardiac surgery 35, 36. However, in our study and others, these markers are commonly elevated at baseline, and thus a relatively large change from baseline (doubling or tripling) would be needed to detect AKI in this setting 37, 38, 39.…”
Section: Discussionmentioning
confidence: 67%
“…Biomarkers of AKI, such as NGAL, KIM‐1, and IL‐18, may be potentially beneficial for early detection, diagnosis, and prognosis of AKI after cardiac surgery 35, 36. However, in our study and others, these markers are commonly elevated at baseline, and thus a relatively large change from baseline (doubling or tripling) would be needed to detect AKI in this setting 37, 38, 39.…”
Section: Discussionmentioning
confidence: 67%
“…23 His hypothesis is supported by recent clinical studies, which demonstrated that two G1 cell cycle arrest markers, namely, insulin-like growth factor-binding protein 7 (IGFBP7) and tissue inhibitor of metalloproteinase 2 (TIMP-2), predicted AKI in critically ill, and cardiac surgical patients. [24][25][26] This adaptive response may be controlled by mitochondria, with the aim to limit further cellular damage and provide cells with the opportunity to recover function. 27 By shutting down some non-essential cellular functions, remaining energy can be directed to other functions that are required for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The major function of this protein is to regulate the availability of insulin-like growth factors (IGFs) in tissue as well as in modulating IGF binding to its receptors. The combination of urinary TIMP-2 and IGFBP7 serves as a sensitive and specific biomarker to predict AKI early after cardiac surgery and to predict renal recovery [17] . Urinary TIMP-2 and IGFBP7 were identified as patients at risk for imminent AKI [18] .…”
Section: Tissue Inhibitor Metalloproteinase-2 and Insulin-like Growthmentioning
confidence: 99%
“…Combination of urinary TIMP-2 and urinary IGFBP7 may be important for clinical adjudication of AKI and risk of kidney failure Identified patients at risk for imminent AKI based on levels of urinary [TIMP-2] * [IGFBP7] [18] Kathleen D. Liu [32] ; Melanie Meersch [17] …”
Section: T-cell Immunoglobulin Domainmentioning
confidence: 99%